2020
DOI: 10.1093/jat/bkaa055
|View full text |Cite
|
Sign up to set email alerts
|

UPLC–MS-Based Procedures to Detect Prolyl-Hydroxylase Inhibitors of HIF in Urine

Abstract: This article presents newly developed screening and confirmation analytical procedures to detect the misuse of nine prolyl-hydroxylase inhibitors of the hypoxia-inducible factor: daprodustat, desidustat, FG2216, IOX2, IOX4, JNJ-42041935, molidustat, roxadustat and vadadustat, targeting either the parent drugs and/or their main metabolite(s). For the sample pretreatment, different extraction protocols and technologies were evaluated. The instrumental analysis was performed by ultra-high-performance liquid chrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 29 publications
0
24
0
Order By: Relevance
“…IOX4 competes F I G U R E 1 Hypoxia-inducible factor (HIF) stabilisers and drug candidates with and displaces 2-oxoglutarate at the active site of prolylhydroxylase-2. 27,31 When compared with IOX2, lower HIFα induction by IOX4 was observed in the liver, heart and kidney; nevertheless, markedly higher induction was observed in the brain.…”
Section: Introductionmentioning
confidence: 99%
“…IOX4 competes F I G U R E 1 Hypoxia-inducible factor (HIF) stabilisers and drug candidates with and displaces 2-oxoglutarate at the active site of prolylhydroxylase-2. 27,31 When compared with IOX2, lower HIFα induction by IOX4 was observed in the liver, heart and kidney; nevertheless, markedly higher induction was observed in the brain.…”
Section: Introductionmentioning
confidence: 99%
“…In light of this, the use of HIF‐PHDs in horses and humans has been strictly prohibited by the International Federation of Horseracing Authorities (IFHA), 17 the Fédération Équestre Internationale (FEI), 18 and in humans by the World Anti‐Doping Agency (WADA) 19 . For the purpose of doping control, a number of analytical methods and metabolism studies for HIF‐PHDs in humans including AKB‐6548, BAY‐348, BAY85–3934, FG‐2216, FG‐4592, and GSK1278863, have been reported by different research groups 10,12,20–26 and mainly by Thevis et al 10,20–24 However, very limited number of reports for IOX4 are available so far in human and horse studies 12,27 . Philip et al recently reported the in vitro metabolic study of IOX4 together with other HIF stabilizers (i.e., IOX2 and IOX3) using equine liver microsomes and the major IOX4 metabolites were identified to be IOX4 glucuronide, O ‐desbutyl IOX4, O ‐desbutyl IOX4 glucuronide, and two forms of mono‐hydroxylated IOX4 27 .…”
Section: Introductionmentioning
confidence: 99%
“…Philip et al recently reported the in vitro metabolic study of IOX4 together with other HIF stabilizers (i.e., IOX2 and IOX3) using equine liver microsomes and the major IOX4 metabolites were identified to be IOX4 glucuronide, O ‐desbutyl IOX4, O ‐desbutyl IOX4 glucuronide, and two forms of mono‐hydroxylated IOX4 27 . Besides, Mazzarino et al reported an excellent analytical method for the detection of IOX4 in human urine but did not study the metabolic fate of IOX4 12 . In this paper, both in vitro and in vivo metabolic studies of IOX4 have been described.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have already been reported on the detectability and metabolic pathway of HIF stabilizers like roxadustat and FG-2216. 7,8 Mazzarino et al 9 have reported a UPLC-MS-based procedure to detect HIF stabilizers in human urine. Beuck et al 10 developed a liquid chromatography (LC)tandem mass spectrometry (MS/MS)-based analytical assay for the determination of HIF stabilizers.…”
mentioning
confidence: 99%